Analysis of Potential Disputes in Taxpayer Status in the Tax Collection Sector - Setiawan, Benny; Anugerah, Bima Satria; Supriyono, Bambang; Wijaya, Andy Fefta; Setyowati, Endah (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the potential for disputes on the status of Taxpayers in Tax Collection. This study was conducted using a qualitative method based on a case study on the Judicial Review Decision Number 503 PK / Pdt / 2020 and 318 / B / PK / Pjk / 2019 regarding the collection of Taxpayers for Taxpayers who make changes to management and go bankrupt. The purpose of the study is to determine the potential for disputes in the future and efforts to anticipate them. The data used are primary data obtained from interviews with informants, documentation and literature studies. The results of the study obtained are that the potential for disputes depends on resistance when collection actions are taken, differences of opinion between the Tax Authorities and Taxpayers or Judges and the weakness of the DGT material in Court. Meanwhile, efforts that can be made to anticipate it are to mitigate risks, anticipate legal efforts, carry out collection actions based on regulations, and conduct internal DGT evaluations.